STANDARD OF LIVING OF THE RUSSIAN POPULATION: FEATURES OF INTERREGIONAL DIFFERENTIATION DYNAMICS - N. A. Gerasimenko (Вестник университета)
The article presents the results of a study of the dynamics of indicators that characterize the standard of living of the population of Federal districts of Russia. The author hypothesizes that despite the growth in the values of indicators of the standard of living of the population of Federal districts for the period after 2010, there is a stable pattern of increasing their differentiation, and he has received its confirmation. This circumstance allowed usto determine the nature of changes and identify two groups of Federal districts that are moving away from each  other at an increasing rate in terms of the standard of living of the population. The analysis raises the issue of the  need to improve the state policy of Russia in order to enhance the standard of living of the population, ensure a balanced socio-economic development of regions and neutralize the negative consequences of their further  differentiation.